Southeast Asian Visual Culture In The Animated Film “Raya And The Last Dragon” - Shienny Megawati Sutanto (Lekesan: Interdisciplinary Journal of Asia Pacific Arts, 2022)
In the year of 2020 “Raya and The Last Dragon” was launched and became part of the Disney Princess animated series. This animated film is rumored to be Disney's first film created based on Southeast Asian visual culture. This study aims to analyze the visual culture of Southeast Asia portrayed in the animated film Raya and The Last Dragon. The research is carried out with qualitative approach, through documentation of previous studies, especially those related to visual culture in Disney Princess animation, as well as direct observation of the film studied. Animated films are a reflection of the thoughts, feelings, and desires of the creators through visual media in the form of signs or semiotics. Therefore, the film Raya and The Last Dragon is analyzed using the semiotic analysis method. These data is strengthened by interviews with cultural experts. The results of this study indicate that Raya and The Last Dragon displays visual signs in the form of settings, costumes, and tools that are a fusion Southeast Asian culture are observable in characterizations, character visualization, to visualization of promotional media of “Raya and the Last Dragon”. However, the visualization is not a genuine representation, and does not properly reflect the visual culture of Southeast Asia.